2016
DOI: 10.1002/acn3.336
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of brain structure and function in neonatal congenital heart disease

Abstract: ObjectiveTo evaluate whether structural and microstructural brain abnormalities in neonates with congenital heart disease (CHD) correlate with neuronal network dysfunction measured by analysis of EEG connectivity.MethodsWe studied a prospective cohort of 20 neonates with CHD who underwent continuous EEG monitoring before surgery to assess functional brain maturation and network connectivity, structural magnetic resonance imaging (MRI) to determine the presence of brain injury and structural brain development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 52 publications
4
30
0
1
Order By: Relevance
“…Although the precise cause of these findings cannot be determined in this pilot study, disorganized connections or a more disperse pattern of thalamocortical connectivity are possible. Birca and colleagues reported decreased low-frequency electroencephalographic connectivity in association with lower FA measurements in the cerebral white matter of neonates with CHD, which supports the hypothesis that our observations may indeed represent abnormalities in emerging cerebral connectivity (45). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the precise cause of these findings cannot be determined in this pilot study, disorganized connections or a more disperse pattern of thalamocortical connectivity are possible. Birca and colleagues reported decreased low-frequency electroencephalographic connectivity in association with lower FA measurements in the cerebral white matter of neonates with CHD, which supports the hypothesis that our observations may indeed represent abnormalities in emerging cerebral connectivity (45). …”
Section: Discussionsupporting
confidence: 88%
“…Birca et al reported decreased lowfrequency electroencephalographic connectivity in association with lower FA measurements in the cerebral white matter of neonates with CHD, which supports the hypothesis that our observations may indeed represent abnormalities in emerging cerebral connectivity. 45 Considering that all CHD neonates in this study were imaged prior to surgery and that there was no acute brain injury at the time of the scan, the observed differences probably developed prenatally. Berman et al reported higher ADC in the thalami of fetuses with CHD imaged during the third trimester relative to controls neonates, which supports that at least in some neonates abnormalities in thalamic microstructure and/or development arise prenatally.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Birca et al. () have shown an interesting association between microstructural brain abnormalities and functional connectivity measured with EEG in patients with CHD. However, further studies are required in order to thoroughly characterise brain connectivity in these infants, and to determine whether there is a pattern of atypical early connectivity that can predict later altered neurodevelopment.…”
Section: The Effect Of Early Adversity – Imaging the Brain At Riskmentioning
confidence: 98%
“…There is now evidence that perturbations in structural and microstructural brain development can result in alterations in neuronal network connectivity in neonates with CHD 67 . Graphic analysis to acquired DTI data recently revealed that differences in the connectome mediate poor neurocognitive function seen in adolescents with d-transposition of the great arteries (d-TGA) repaired during infancy 68 .…”
Section: Neuroimaging In Chdmentioning
confidence: 99%